Contemporary Medical Management of Primary Hyperparathyroidism: A Systematic Review - Leere, Julius Simoni; Karmisholt, Jesper; Robaczyk, Maciej; Vestergaard, Peter (Frontiers in Endocrinology, 2017)
Introduction: Primary hyperparathyroidism is increasingly an asymptomatic disease at diagnosis, but the recognized guidelines for management are based on evidence obtained from studies on patients with symptomatic disease, and surgery is not always indicated. Other patients are unable to undergo surgery, and thus a medical treatment is warranted. This systematic review provides an overview of the existing literature on contemporary pharmaceutical options available for the medical management of primary hyperparathyroidism. Methods: Databases of medical literature were searched for articles including terms for primary hyperparathyroidism and each of the included drugs. Data on s-calcium, PTH, bone turnover markers, bone mass density and hard endpoints were extracted and tabulated, and level of evidence was determined. Changes in s-calcium were estimated and a meta-regression analysis was performed. Results: 1999 articles were screened for eligibility and 54 were included in the review. Weighted mean changes calculated for each drug in s-total calcium (mean change from baseline ± SEM) were: Pamidronate:(0.31 ± 0.034 mmol/l); Alendronate: (0.07 ± 0.05 mmol/l); Clodronate: (0.20±0.040 mmol/l); Mixed bisphosphonates: (0.16 ± 0.049 mmol/l); and Cinacalcet: (0.37 ± 0.013 mmol/l). The meta-analysis revealed a significant decrease of effect on s-calcium with time for the bisphosphonates (Coef. -0.049±0.023, p=0.035), while cinacalcet proved to maintain its effect on s-calcium over time. Bisphosphonates improved BMD while cinacalcet had no effect. Discussion: The included studies demonstrate advantages and drawbacks of the available pharmaceutical options that can prove helpful in the clinical setting. The great variation in how primary hyperparathyroidism is manifested requires that management should rely on an individual evaluation when counseling patients. Combining resorptive agents with calcimimetics could prove rewarding, but more studies are warranted.